2016
DOI: 10.1118/1.4966699
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐energetic cross talk in photon counting detectors: Detector model and correlated Poisson data generator

Abstract: The authors have developed a novel, computationally efficient PCD model that takes into account double-counting and resulting spatio-energetic correlation between PCD pixels. The MC simulation validated the accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 46 publications
0
66
0
Order By: Relevance
“…We simulated charge sharing according to the uniform spherical charge cloud model of Taguchi, where the diameter d of the charge cloud is related to the deposited energy E as d=d0(E/Enormalref)1/3, and we used d0=30μm at Enormalref=70keV. By dividing the detector into 0.5×0.5mm2 pixels and calculating the charge cloud volume fraction located within the borders of each pixel, we obtained the total charge collected in each pixel.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We simulated charge sharing according to the uniform spherical charge cloud model of Taguchi, where the diameter d of the charge cloud is related to the deposited energy E as d=d0(E/Enormalref)1/3, and we used d0=30μm at Enormalref=70keV. By dividing the detector into 0.5×0.5mm2 pixels and calculating the charge cloud volume fraction located within the borders of each pixel, we obtained the total charge collected in each pixel.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have been published on how to model the frequency‐dependent detective quantum efficiency of photon‐counting detectors, but these studies do not take energy information into account. At the same time, the impact of detector nonidealities on spectral imaging tasks has been studied by several authors . However, these publications only study the zero‐spatial‐frequency performance and do not investigate the frequency‐dependent spectral performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used r ¼ 40 lm, independent of energy, except when stated otherwise in a sensitivity analysis (described later). Two other models described in the literature include a small sphere with radius 15 lm at 70 keV, where the radius grows as a cube root of the energy, 29 and a larger sphere with radius 50 lm at 60 keV that linearly increases to a radius of 75 lm at 120 keV, 30 but other models also exist. 25 An experimental study found the best fit with a Gaussian charge cloud with r = 30 lm, which is slightly better than our choice of 40 lm.…”
Section: B Monte Carlo Simulationsmentioning
confidence: 99%
“…The use of small sub‐pixels will benefit count rate capability; however, it increases chances of one photon being counted multiple ( n ) times by neighboring pixels due to charge sharing, fluorescence x‐ray emission and reabsorption, and Compton scattering . It is called double‐counting when n = 2 or n ‐tuple‐counting for n in general and it may increase the variance of PCD data.…”
Section: Introductionmentioning
confidence: 99%